Environmental Management Strategies for Cost-Effective Waste Management in Hospitals: Strategi Manajemen Lingkungan untuk Pengelolaan Limbah Rumah Sakit yang Hemat Biaya - Mujiawati, Gishelia Anastasya; Hadiah Fitriyah (Indonesian Journal of Law and Economics Review, 2024)
General background: Waste management in hospitals is crucial due to its environmental impact. Specific background: RSU Al Islam HM Mawardi Krian struggles with waste management while adhering to PSAP No. 1 of 2010 and maintaining efficiency. Knowledge gap: Limited research exists on applying environmental management accounting and operational strategies for hospital waste management in line with accounting standards. Aims: This study analyzes the impact of environmental management accounting and strategies on waste management costs at RSU Al Islam HM Mawardi Krian, assessing compliance with PSAP standards. Results: The hospital has implemented processes of identification, recognition, measurement, recording, presentation, and disclosure per PSAP No. 1 of 2010, managing waste effectively and incurring environmental costs. Novelty: Offers insights into aligning hospital environmental cost management with government standards. Implications: Structured environmental accounting and strategies can enhance waste management, improve hospital reputation, ensure regulatory compliance, and potentially increase revenue. Highlights: RSU Al Islam HM Mawardi complies with PSAP No. 1 of 2010 in managing waste costs. Proper environmental accounting improves transparency and operational efficiency. Structured strategies can boost hospital reputation and revenue. Keywords: Environmental Management Accounting, Operational Strategies, Waste Management Costs, Hospital Compliance